Análise de índices de qualidade de água da bacia hidrográfica apodi-mossoró - Vale, Rudna Angelica Vieira do (2020)
The hydrographic basins located in the semi-arid region suffer from the low rate and seasonality of rains, great evaporation due to high temperatures, in addition to being predominantly low-volume and low flow. The Apodi-Mossoró basin has these attributes and, under these circumstances, efficient water resource management is essential. The water quality monitoring activity supports the decision-making about its use, and is carried out through the periodic measurement of qualitative indicators. Based on the data from the Água Azul Program regarding the Apodi-Mossoró basin, collected from 2008 to 2016, this research aims to make a temporal analysis of the behavior of the basin regarding the Trophic State Index - TSI and salinity, as well as applying the multivariate statistical method of Principal Component Analysis - PCA for the WQI index - Water Quality Index to show, among the nine indicators that make up the calculation, which ones have greater participation in the content of this index. The results indicate that the basin suffers interposition from the rain seasonality, linked to high temperatures, and also from the intense anthropic activity in the course of the river, as shown by the responses of the TSI, having mostly hypereutrophic behavior, and increasing salinity at the end of the period. collects, between 2014 and 2016, that these are followed by years of drought. The IQA indicator PCA corroborates these facts, since the outstanding indicators were temperature, total nitrogen, BOD and total solids, the last three being individual pollution indicators. Finally, the investigation points, without detailing, to an inefficiency in the management of the Apodi-Mossoró River basin